Valuation of Family Firms: The Limitations of Accounting Information. Issue 2 (12th June 2013) - Hasso, Tim; Duncan, Keith
<x xml:space="preserve">Abstract</x> This conceptual paper explores the extent to which reported accounting information captures unique family firm decision‐making and intangible asset factors that impact financial value. We review the family firm valuation‐relevant literature and identify that this body of research is predicated on the assumption that accounting information reflects the underlying reality of family firms. This research, however, fails to recognise that current accounting technology does not fully recognise the family firm factors in the book value of the firm or the implications for long‐run persistence of earnings. Thus, valuation models underpinning the extant empirical research, which are predicated on reported accounting information, may not fully reflect the intrinsic value of family firms. We present propositions on the interaction between accounting information, family factors and valuation as a road map for future empirical research with a discussion of appropriate methodologies.